Pengaruh Perencanaan Pajak dan Capital Intensity Terhadap Penghindaran Pajak (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Devi Damasti Andhara Putri (Yayasan Literasi Ilmiah Indonesia, 2023)
Purpose: This study aims to examine tax planning and capital intensity on tax avoidance Method: The sampling technique used purposive sampling method based on certain criteria. The sample used in this study amounted to 14 mining sector companies for the period 2018-2020 which produced 42 sample data. Finding: Based on the data analysis that has been done, the results of the research show that tax planning has a negative effect on tax avoidance and capital intensity has a positive effect on tax avoidance. Novelty: This study integrates several topics regarding tax avoidance variables which are influenced by two variables, namely tax planning and capital intensity Keywords: Tax Planning, Capital Intensity, Tax Avoidance